MODALITAS HAZU BAHASA JEPANG DAN SEHARUSNYA BAHASA INDONESIA (KAJIAN KONTRASTIF) - Nurzavika Nurzavika; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research discuss about contradiction and similarity of meaning of hazu da modality in Japanese language and seharusnya in bahasa. This research uses the Heiko Narrog (2019) and Hasan Alwi (1992) theory as the study of qualitative descriptive. This data research is discover from the news website with scrutinize, record, and note way the hazu da dan seharusnya sentences. The results show that the difference of meaning of hazu da modality and seharusnya modality, which mean the fervent assumption or conviction, only can clarify of one conclution by a powerful evidence basis, clarifying of the pronouncement by the speaker who have authority and have responsibility of what it discourse, to clarify the assumption which related to proper thing’s, to clarify the order to someone elses to do something, to clarify the order with the higest retiksion degree, and that clarification it must come from by it self. The similarity of meaning of hazu da modality and seharusnya modality is having the same meaning of withdrawal the clarified with the logical conclusion, the meaning to clarify of the pronouncement it linked with something was happened, clarify then the opinion and exactly the same that have no meaning to clarified of some prejudice.Key Words: Modality, Contradiction And Similarity, Mean